Normal glutamate but elevated myo-inositol in anterior cingulate cortex in recovered depressed patients - Taylor, M; Selvaraj, S; Norbury, R; Jezzard, P; Cowen, P (Elsevier, 2009)
Background: MRS studies of acutely depressed patients reveal decreased levels of total glutamate and glutamine (Glx) in frontal cortex which may reflect abnormalities of glutamate-glutamine cycling through astrocytes. Frontal Glx levels appear to be normalised after recovery from depression, but it is not known if this composite measure masks ongoing differences in glutamate or glutamine alone. Methods: Medication-free, fully recovered patients with a history of DSM-IV recurrent major depressive disorder (n=14) and healthy controls (n=16) were scanned at 3T. Short echo time PRESS and PRESS-J spectra were acquired from a 12 cm(3) voxel of frontal cortex incorporating the anterior cingulate. Results: Levels of Glx and of glutamate alone did not differ between groups. However, myo-inositol concentrations were significantly higher in those with a history of depression than in controls. LIMITATIONS: Abnormal MRS measures were not demonstrated during episodes of depression for these participants, so any evidence of changes with recovery is indirect. Conclusions: The normal glutamatergic measures combined with elevated levels of the astrocytic marker, myo-inositol, suggest that recovery from depression may be associated with changes in glial function in frontal cortex.